PERBEDAAN KEMAMPUAN MENYUNTING KARANGAN DENGAN METODE JIGSAW DAN INKUIRI KELAS IX MTsN BARIANG RAO-RAO - DIAN SARMITA (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This study aims to determine differences in the ability to edit the essay using the type cooperative jigsaw and inquiry method class IX students MTsN Bariang Rao-rao South Solok. This research is a quantitative research using experimental quasy. The sample in this study consisted of two classes are taken by using random sampling techniques, the class and the class IX.4 IX.3. Data collected through performance tests. Based on the analysis of data, the results are as follows. First, the ability to edit an essay of students taught by cooperative method jigsaw type the experimental class I was not much different than students who are taught by the method of inquiry in the experimental class II, with an average ratio of the two classes, namely 85 and 82. Second, the ability to edit the essay of the students who have a high initial ability taught by jigsaw type co-operative method in experimental class is different than the students class I have taught with high initial capability with the method of inquiry in the experimental class II, with an average ratio of the two classes, namely 90 and 85. Third, the ability to edit essay on the student who has the lower initial ability taught by jigsaw type co-operative method in the experimental class I was not much different than the student has the ability to lower initial taught by method of inquiry in the experimental class II, with an average ratio of the two classes, namely 84 and 81. Fourth, there is no interaction between prior knowledge with learning methods in affecting the ability of editing. ABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan kemampuan menyunting karangan dengan menggunakan metode kooperatif tipe jigsaw dan metode inkuiri siswa kelas IX MTsN Bariang Rao-rao Kabupaten Solok Selatan. Jenis penelitian ini adalah penelitian kuantitatif dengan menggunakan metode quasy eksperiment. Sampel dalam penelitian ini terdiri dari dua kelas yang diambil dengan menggunakan teknik random sampling, yaitu kelas IX.3 dan kelas IX.4. Pengumpulan data dilakukan melalui tes unjuk kerja. Berdasarkan hasil analisis data, diperoleh hasil sebagai berikut. Pertama, kemampuan menyunting karangan siswa yang diajar dengan metode kooperatif tipe jigsaw pada kelas eksperimen I tidak jauh berbeda daripada siswa yang diajar dengan metode inkuiri pada kelas eksperimen II, dengan perbandingan rata-rata kedua kelas, yaitu 85 dan 82. Kedua, kemampuan menyunting karangan pada siswa memiliki kemampuan awal tinggi yang diajar dengan metode kooperatif tipe jigsaw pada kelas eksperimen I berbeda daripada siswa memiliki kemampuan awal tinggi yang diajar dengan metode inkuiri pada kelas eksperimen II, dengan perbandingan rata-rata kedua kelas yaitu 90 dan 85. Ketiga, kemampuan menyunting karangan pada siswa memiliki kemampuan awal rendah yang diajar dengan metode kooperatif tipe jigsaw pada kelas eksperimen I tidak jauh berbeda daripada siswa memiliki kemampuan awal rendah yang diajar dengan metode inkuiri pada kelas eksperimen II, dengan perbandingan rata-rata kedua kelas yaitu 84 dan 81. Keempat, tidak terdapat interaksi antara kemampuan awal dengan metode pembelajaran dalam mempengaruhi kemampuan menyunting.